Model-based Business Cycle and Financial Cycle Decomposition for Europe and the U.S. - Siem Jan Koopman; Rutger Lit; Andre Lucas (Tinbergen Institute, 2016)
We develop a multivariate unobserved components model to extract business cycle and financial cycle indicators from a panel of economic and financial time series of four large developed economies. Our model is flexible and allows for the inclusion of cycle components in different selections of economic variables with different scales and with possible phase shifts. We find clear evidence of the presence of a financial cycle with a length that is approximately twice the length of a regular business cycle. Moreover, cyclical movements in credit related variables largely depend on the financial cycle, and only marginally on the business cycle. Property prices appear to have their own idiosyncratic dynamics and do not substantially load on business or financial cycle components. Systemic surveillance policies should therefore account for the different dynamic components in typical macro financial variables.
Keywords: E32; C22; 330; financial cycle; business cycle; phase shift; multivariate state space model; Kalman filtering; panel time series